Examining maternal influences on low birth weight of baby: a study in Washim district - Kore, Suhas; Kukade, Rajesh; Ugaonkar, Vinita (International Journal Of Community Medicine And Public Health, 2023)
Background: This research investigated low birth weight (LBW) in Washim district, Maharashtra, India, recognizing its profound impact on infant health. With a prevalence of 13.3%, lower than state and national averages, the study focuses on maternal factors such as anemia, premature deliveries, and inadequate weight gain during pregnancy as contributors to LBW. Methods: A cross-sectional study involving LBW infants and mothers was conducted in Washim district. The census approach (universal sampling) was employed in this study, encompassing the entire population of low birth weight babies born across all blocks in the Washim district and could be tracked by healthcare workers. This involved every eligible individual, eliminating the need for traditional sampling techniques. Data were collected from 6 Blocks, 153 Health sub-centers, and 25 primary health centers between April 1, 2022, and March 31, 2023, using a standardized questionnaire administered by healthcare workers. The study included 876 babies and mothers. Results: Washim district reported a 13.3% LBW rate, lower than the state (20.1%) and national (17.8%) averages. High LBW incidence was noted among mothers with anemia (91.4%), premature deliveries (78.18%), and inadequate weight gain during pregnancy (average gain: 7.9 kg). Conclusions: The study identified anemia during pregnancy, premature deliveries, and inadequate weight gain as primary contributors to LBW in the district.